Change in the Structure of Escherichia coli Population and the Pattern of Virulence Genes along a Rural Aquatic Continuum - Petit, Fabienne; Clermont, Olivier; Delannoy, Sabine; Servais, Pierre; Gourmelon, Michèle; Fach, Patrick; Oberlé, Kenny; Fournier, Matthieu; Denamur, Erick; Berthe, Thierry (Frontiers in Microbiology, 2017)
The aim of this study was to investigate the diversity of the E. coli population, focusing on the occurrence of pathogenic E. coli, in surface water draining a rural catchment. Two sampling campaigns were carried out in similar hydrological conditions (wet period, low flow) along a river continuum, characterized by two opposite density gradients of animals (cattle and wild animals) and human populations. While the abundance of E. coli slightly increased along the river continuum, the abundance of both human and ruminant-associated Bacteroidales markers, as well as the number of E. coli multi-resistant to antibiotics, evidenced a fecal contamination originating from animals at upstream rural sites, and from humans at downstream urban sites. A strong spatial modification of the structure of the E. coli population was observed. At the upstream site close to a forest, a higher abundance of B2 phylogroup strains was observed. At the pasture upstream site, a greater proportion of both E and B1 phylogroups was detected, therefore suggesting a fecal contamination of mainly bovine origin. Conversely, in downstream urban sites, A, D, and F phylogroups were more abundant. To assess the occurrence of intestinal pathogenic strains, virulence factors (afaD, stx1, stx2, eltB (LT), estA (ST), ipaH, bfpA, eae, aaiC and aatA) were screened among 651 E. coli isolates. Intestinal pathogenic strains STEC O174:H21 (stx2) and EHEC O26:H11 (eae, stx1) were isolated in water and sediments close to the pasture site. In contrast, in the downstream urban site aEPEC/EAEC and DAEC of human origin, as well as extra-intestinal pathogenic E. coli belonging to clonal group A of D phylogroup, were sampled. Even if the estimated input of STEC (Shiga toxin-producing E. coli) – released in water at the upstream pasture site – at the downstream site was low, we show that STEC could persist in sediment. These results show that, the run-off of small cattle farms contributed, as much as the wastewater effluent, in the dissemination of pathogenic E. coli in both water and sediments, even if the microbiological quality of the water was good or to average quality according to the French water index.